Energy transition strategies in Portugal: Wind and solar externalities on municipalities housing prices - Robaina, M.; Lima, F.; Miguel, T.; Ramalho, E.; Hayaka, K. I.; Madaleno, M.; Dias, M. F.; Meireles, M.; Botelho, A. (International Journal of Housing Markets and Analysis, 2026)
Purpose This paper aims to investigate the impact of wind and solar farms on housing prices in Portugal to better understand their role in shaping social acceptance. Design/methodology/approach Fixed-effects models with Driscoll–Kraay standard errors are estimated using municipal-level panel data for 177 municipalities from 2011 to 2022. Renewable energy deployment is captured through three measures: presence, number of farms and installed capacity (MW) of wind and solar power. Findings Results indicate that wind farms generally do not affect housing prices. However, for each additional MW of installed wind capacity, the median housing price decreases, on average, by €1.11/m2. By contrast, solar farms are linked to higher housing values, with municipalities hosting solar farms exhibiting average housing prices €28.51/m2 above those without. Practical implications Findings highlight the importance of accounting for housing market externalities in renewable energy planning to foster social acceptance and improve policy design. Originality/value This study examines how wind and solar energy projects may affect housing markets in Portugal, a country simultaneously leading the energy transition and experiencing sharp increases in housing prices. It also contributes methodologically by using municipal-level aggregated data, providing a broader perspective than studies focused on micro-level or property-specific data.